Cellular Generation Number as an Invariant Measure of Biological Time in Relativistic Systems: Biological Systems do Not Experience Time Dilation (London Journal of Research In Science: Natural and Formal, 2025)
This work presents a thought experiment where the number of cellular duplications or generations (G) is used as a biological clock to investigate the effects of relativistic environments on biological time. We demonstrate that, although physical clocks in different reference systems measure varying times due to relativistic time dilation, biological time remains invariant and corresponds to the proper time. This invariance holds not only across inertial reference frames but also extends to non-inertial, accelerated, and gravitational reference systems. The invariance arises because G is defined as the ratio of the growth time to the duplication time, ensuring that any relativistic effects influencing these time intervals cancel out.These findings challenge the classic interpretation of Einstein's twin paradox, which suggests differential ageing due to relativistic velocities. In reality, while physical clocks indicate differing times, biological time, and thus the biological age of living organisms, remains unaffected, aligning consistently with the proper time. Although bacterial cultures were used as a model in this study, the results are generalisable to all cellular systems, provided identical growth conditions are maintained. This study provides new insights into the interplay between biological processes and relativistic effects, establishing G as a reliable and invariant measure of biological time across all reference frames
Keywords: Northern Harrat Rahat; Transitional crust; Elastic constants; Rheological properties; low-velocity and density zone; geothermal favorability.; time dilation; twin paradox; Biological time; Biological clock; Relativistic effects; Proper time; Invariant ageing